Predictive Value of the Triglyceride-Glucose Index for Metabolic-Associated Fatty Liver Disease in Individuals with Different Metabolic Obese Phenotypes - Lv D; Wang Z; Liu H; Meng C (Diabetes, Metabolic Syndrome and Obesity)
Dan Lv,1 Zepu Wang,2 Huanxin Liu,1 Cuiqiao Meng1 1Physical Examination Center, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Hepatobiliary Surgery, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Dan Lv, Physical Examination Center, Hebei General Hospital, 348 heping West Road, Shijiazhuang, Hebei, People’s Republic of China, Email ld2449@163.comObjective: To investigate the relationship between triglyceride-glucose (TyG) index and metabolic-associated fatty liver disease (MAFLD), and to evaluate the predictive value of the TyG index for MAFLD in individuals with different metabolic obese phenotypes. The aim is to provide a novel approach for the screening and early diagnosis of MAFLD in the general population.Methods: A total of 2614 subjects were recruited and classified into four categories of metabolic obese phenotypes based on their body mass index (BMI) and metabolic status. Basic data and general blood indices were collected and analyzed. The TyG index was calculated, and an abdominal ultrasound was performed to detect the presence of fatty liver disease. The aforementioned data were then subjected to statistical analysis.Results: The TyG index was significantly higher in the MAFLD group than in the non-MAFLD group (P < 0.001). Furthermore, the TyG index in the metabolically unhealthy and obese (MUO) group and the metabolically unhealthy normal weight (MUNW) group was significantly higher than that in the metabolically healthy and obese (MHO) group and the metabolically healthy normal weight (MHNW) group (P < 0.001). The area under the curve (AUC) of the TyG index for predicting MAFLD in the MHNW, MUNW, MHO, and MUO groups was 0.765, 0.766, 0.659, and 0.650, respectively. The critical values were 8.575, 9.075, 8.795, and 9.165, respectively.Conclusion: The TyG index is a reliable predictor of MAFLD risk, exhibiting a higher predictive ability for the risk of developing MAFLD in individuals with normal BMI compared to those with abnormal BMI. The findings of this study lend support for the use of the TyG index as a screening tool and for guiding subsequent management of patients with MAFLD.Keywords: TyG index, MAFLD, metabolic obese phenotype, screening, predictive value